2019
DOI: 10.1111/pce.13670
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA demethylation enhances plant tolerance to cadmium toxicity by improving iron nutrition

Abstract: Although the alteration of DNA methylation due to abiotic stresses, such as exposure to the toxic metal cadmium (Cd), has been often observed in plants, little is known about whether such epigenetic changes are linked to the ability of plants to adapt to stress. Herein, we report a close linkage between DNA methylation and the adaptational responses in Arabidopsis plants under Cd stress. Exposure to Cd significantly inhibited the expression of three DNA demethylase genes ROS1/DML2/DML3 (RDD) and elevated DNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 79 publications
3
32
0
1
Order By: Relevance
“…The mapping efficiency obtained is comparable to the informed in other WGBS studies [16,[48][49][50]. Likewise, the proportion of the three-methylation context in the transgenic tobaccos was similar to those reported in other plant models as soybean [51], barrel clover [7], maize [16], Arabidopsis [21,50], tomato [52], burberry [48] and watermelon [49], among others. In all these studies, the higher methylation levels were located in the CG context.…”
Section: Discussionsupporting
confidence: 87%
“…The mapping efficiency obtained is comparable to the informed in other WGBS studies [16,[48][49][50]. Likewise, the proportion of the three-methylation context in the transgenic tobaccos was similar to those reported in other plant models as soybean [51], barrel clover [7], maize [16], Arabidopsis [21,50], tomato [52], burberry [48] and watermelon [49], among others. In all these studies, the higher methylation levels were located in the CG context.…”
Section: Discussionsupporting
confidence: 87%
“…It was reported that the DNA demethylase DML2 was downregulated under cold stress in tomato, which resulted in the hypermethylation of the promoter and silencing of genes involved in the biosynthesis of flavor volatiles 41 . Moreover, Cd-induced lower expression of three DNA demethylase genes ( ROS1 , DML2 and DML3 ) resulted in higher DNA methylation in Arabidopsis 39 . In this study, RT-qPCR analysis of DNA demethylase genes showed that RsROS1 was downregulated in Pb200 and upregulated in Pb_50MT, while RsDME presented higher expression levels in Pb200 than in Control, indicating that these genes may play a major role in decreasing the methylation level after MT treatment (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In rice in response to Cd stress, the methylation level of genes was changed, followed by altered expression levels, and 5-azacytidine promoted growth and Cd accumulation by enhancing the transcription of genes involved in HM transport 12 . Exposure to Cd elevated DNA methylation at the genome-wide level in Arabidopsis roots 39 . In the present study, the genome-wide DNA methylation level was increased under Pb stress and obviously reduced after 50 μM MT treatment (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, little information has been reported to show how Zn‐ and Cd‐induced DNA and protein methylation regulate Zn and Cd accumulation and tolerance in plants: Fan et al . (2020) showed that DNA demethylation enhances plant tolerance to Cd toxicity in A. thaliana , while Serre et al . (2020) pointed out differences in the Lys methylation of nonhistone proteins in two Cd‐sensitive species, A. thaliana and A. lyrata , and in three populations of A. halleri AU, I16 and PL22 with contrasting Cd accumulation and tolerance.…”
Section: Discussionmentioning
confidence: 99%